Gender Diversity and Performance in Family Small-to-Medium Business: Mapping and Clustering Bibliometric Networks - Naciti, Valeria; Rupo, Daniela; Pulejo , Luisa (Piccola Impresa / Small Business, 2022)
Over the past few years, companies have increasingly begun to consider inclusion and gender diversity as a source of competitive advantage and in particular as a key factor for growth. In recent years, the available data show that the involvement of women in the governance of family businesses is more pronounced than in non-family businesses. Although prior literature has addressed the topics of gender diversity and performance in large and medium enterprises, less attention has been posed to family SMEs and on the evolution of studies that analyze such relationships. According to such evidence, this paper seeks to grasp the connections between gender diversity in family SMEs and performance. Bibliometric analysis has been conducted on 125 articles published during the period 1999–2021. The keywords analysis reveals the existence of three independent clusters of research which can be traced back to the following three topics: Corporate Governance and Performance (Green Cluster), Entrepreneurship (Blue Cluster), and Strategy (Red Cluster). In each of these clusters, it is possible to identify key aspects of women's profile within family SMEs. This study offers valuable results both from the academic and business perspective. The bibliometric analysis clearly illustrates the different stages of this field of study, as well as the emerging lines of research, which can be studied in greater depth.